2015
DOI: 10.1007/s13201-015-0297-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of groundwater quality by unsaturated zone study due to migration of leachate from Abloradjei waste disposal site, Ghana

Abstract: Leachate generated by open solid waste disposal sites contains substances likely to contaminate groundwater. The impact of potential contaminants migrating from leachate on groundwater can be quantified by monitoring their concentration and soil properties at specific points in the unsaturated zone. In this study, physical and chemical analyses were carried out on leachate, soil and water samples within the vicinity of the municipal solid waste disposal site at Abloradjei, a suburb of Accra, Ghana. The area ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…High nitrate concentration in leachate could be attributed to the presence of household and agricultural wastes in a landfill. Phosphate is released in leachate mainly due to the degradation of organic matter that contain phospholipids and phosphoproteins and from the dumping of pesticide residues and phosphate fertilizers in landfill [39,40]. Fatta et al [39] reported phosphate concentration from an old landfill in Greece which varied from 9.7 to 16.8 mg/L.…”
Section: Physico-chemical Characteristics Of Landfill Leachate and Mu...mentioning
confidence: 99%
“…High nitrate concentration in leachate could be attributed to the presence of household and agricultural wastes in a landfill. Phosphate is released in leachate mainly due to the degradation of organic matter that contain phospholipids and phosphoproteins and from the dumping of pesticide residues and phosphate fertilizers in landfill [39,40]. Fatta et al [39] reported phosphate concentration from an old landfill in Greece which varied from 9.7 to 16.8 mg/L.…”
Section: Physico-chemical Characteristics Of Landfill Leachate and Mu...mentioning
confidence: 99%